Strategy The Effect of Marketing and Digital Literacy Through Social Media Marketing on Visiting Decisions - Septiandari, Fika; Wardoyo, Cipto; Wardana3, Ludi Wishnu (PT FORMOSA CENDEKIA GLOBAL, 2024)
icient in varioThis study aims to determine the significant influence between variables, following the hypothesis in this study. This research has both theoretical and practical benefits to the world of education, especially concerning marketing strategies and visiting decisions in educational tourism. This research uses a quantitative approach with descriptive research methods. The population in this study were all visitors to the Kampung Coklat educational tour whose numbers were not known with certainty while the sample used in this study was 222 respondents. The sampling technique in this study is classified as a non-random / non-probability sampling method with incidental sampling. The results showed that there was a direct and significant positive influence between Marketing Strategy on Visiting Decisions. In addition, there is a direct and significant positive influence between Digital Literacy on Visiting Decisions. The ability to use technology and information from digital devices is very helpful to be more effective and effus tourism marketing contexts that collaborate with YouTube, TikTok, and Instagram. Furthermore, there is a direct and significant positive influence between Marketing Strategy on Social Media Marketing. In addition, there is no influence between Digital Literacy on Media Social Marketing.